FAKTOR-FAKTOR KEDISIPLINAN KARYAWAN TERHADAP PENINGKATAN UNIT USAHA TOKO PUTRI DI PONDOK PESANTREN AL-MASHDUQIAH - Maidah Sufiani (IZZI: Jurnal Ekonomi Islam, 2022)
The purpose of this study is to find out and analyze the factors of employee discipline towards the improvement of the women's shop business unit at the Al-Mashduqiah Islamic Boarding School. This research is a type of descriptive qualitative research, for research data collection includes observations and interviews with certain parties. As for the results of interviews with the head of the Putrid store unit, supervisors and employees about the factors of employee discipline to the improvement of Putrid stores, namely the influence of the presence of a finger to determine whether the employee is present or not, the firmness of the leadership in a business unit, the firmness of the leader to employees and legal sanctions. The unit effectively enforced the finger. Initially, the salary of the employee from the head of the business unit was transferred to the financial institution of the Islamic boarding school so that the finger became evidence of the absence of the employees so that sanctions or salary cuts were immediately deducted for employees who did not comply with the regulations set by the caregivers and members of the Kopontren . Al-Mashduqiah Islamic Boarding School's girls shop developed not only because of the finger or manual absence, but because of employee performance, employee enthusiasm and motivation from caregivers so that the girls' shop has grown to this day.